Microbial mechanism of zinc fertilizer input on rice grain yield and zinc content of polished rice - Xiao, Yang Sean; Zhou, Bo; Han, Zhuangzhuang; Liu, Shenzhou; Ding, Can; Jia, Feifei; Zeng, Wenzhi (Frontiers in Plant Science, 2022)
Zinc is an essential minor element for rice growth and human health. Applying Zn fertilizer to rice (Oryza sativa L.) is an effective way to boost yield and grain zinc content. As the most active component in soil, microorganisms can realize a virtuous cycle of soil nutrients and crop growth. However, current studies on the impacts of Zn fertilizer application on crop yield and grain Zn content are inconsistent. The mechanism during the process, especially concerning the soil bacterial community characteristics, is yet unclear. Therefore, it’s important to have a comprehensive understanding of the rice rhizosphere bacterial communities. We took advantage of 16S rRNA gene sequencing and co-occurrence network analysis to study the effects of Zn fertilizer application on the rice grain yield, Zn content and the soil bacterial community. Results showed that Zn application (ZS2, i.e., 10.35 kg ha-1 Zn soil application + 3.10 kg ha-1 foliar spraying) increased the grain yield (17.34%~19.52%) and enriched the Zn content of polished rice (1.40%~20.05%) compared with the control group (ZS0) treatments. This was closely correlated to the soil available Zn (AZ) content (1.16%~85.69%). Furthermore, soil total nitrogen (TN) was considered as the primary driver that led to a community shift in the rice rhizosphere bacterial community. This was mainly due to the variation in the co-occurrence network which was made more complex and stable by the Zn fertilizer application. Thus, the interaction between different species was strengthened. During the process, the most critical bacterial taxa were identified as Actinobacteria, Bacteroidetes, Proteobacteria, and Chloroflexi. KEGG metabolic pathway prediction demonstrated that Zn application may improve metabolism functions such as lipid metabolism, amino acid metabolism, carbohydrate metabolism, and xenobiotics biodegradation, which may ultimately affected the yield and Zn content of rice grains. However, their positive effects were different among rice cultivars, of which Nanjing-9108 performed better. This study deepens the understanding of the interaction between Zn fertilizer, rice yield, Zn content of rice grain, and soil bacterial structure and further navigates the development of Zn-rich rice cultivation strategies.